Global Civil Society and Its Limits
XIV, 279 p. 4 illus.
Keywords: This volume critically examines the promise of a global civil society. Exploring issues in cases of diverse social justice movements, the contributors show that a global civil society is still far from emerging and its promotion may even harm the realization of grassroots democracy. The Internet is an exciting new means for activists to communicate internationally, and citizens' movements increasingly co-ordinate campaigns through transnational advocacy networks, but most effective civic action still takes place at national and local levels.